A third wave of European education policy: Transnational and national conceptions of knowledge in Swedish curricula - Wahlström, Ninni (European educational research journal EERJ, 2016)
The aim of this article is to examine how transnational concepts within educational policies influence national curricula in the reconceptualisation of educational policy into concrete curriculum texts. Based on a critical discourse analysis and the concepts of recontextualisation, convergence and divergence, a third wave of European policy discourse has been identified, emphasising an increasing interest in compulsory school and curriculum. Analyses of policies and pedagogical texts show a convergence between a European and a Swedish knowledge discourse concerning standards, basic skills and a performance-based curriculum; however, there is a divergence in terms of transversal skills in transnational policy documents compared to an emphasis on school subjects in the Swedish curriculum. In the transnational arena, the concept of knowledge is mainly interpreted in terms of competencies, while in the Swedish curriculum – the Curriculum for the Compulsory School, Preschool Class and the Leisure-Time Centre 2011 – knowledge is understood in more traditional terms and includes abilities within subjects.